The Concept of Corporate Social Responsibility in Islamic Banking from the Perspective of Islamic Economics - Najachah, Elysa (Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
Purpose - This paper aims to give an alternative to the CSR concept in Sharia banking is appropriate to rule in economy Islam.Method - This paper uses qualitative study through understanding in a way inductive. The approach used is through approach related to normative theology CSR concept in the economy of Islam.Result - CSR in Sharia banking is implemented following the rule economy Islam that is with aqad that complies with Sharia, is legal, and is also transparent in CSR disclosure. Besides that, the CRS concept in Sharia banking can also be used to guard faith, soul, offspring, protecting the mind, and wealth through connection with Allah (hablum min Allah) and also relationships with humans ( hablum Minannas ). As a consequence of the implementation draft, the threat boycott can avoided. This CSR concept is also a form of commitment to Islamic banking to contribute to the field economy, quality communication, and quality of life legally and ethically.Implication - Results study This shows that the concept of CSR in Sharia banking is appropriate with rule economy Islam can contribute to improvement investment, image positive, and loyalty of customers and employees in Syariah banking.Originality - throughout knowledge author, research This is the first study to discuss in a way detailed and systematic related CSR concept in Islamic banking perspective economy Islam.